DIETARY POLYPHENOL COMBINATION POTENTIATES ANTIHYPERGLYCEMIC EFFECT OF GLIMEPIRIDE IN EXPERIMENTALLY INDUCED DIABETES IN RATS - Dhonde Satish*, Dhawale Shashikant, Deshmane Gorakh (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2023)
Diabetes mellitus (DM) is one of the leading causes of morbidity and mortality all over the world. The application of a traditional system of medicine in the treatment of DM is having a boom in recent years. The use of phytochemicals like quercetin, resveratrol, gallocatechin, rutin, gallic acid, and genestin has a beneficial effect in the management of the severity of DM and related complications and the combined effect of these phytochemicals is need to be evaluated. In present research antidiabetic activity of quercetin (Q) and resveratrol (R) alone and in combination were tested in the presence and absence of modern antidiabetic agents on the alloxan-induced DM and associated complications. Alloxan monohydrated (120 mg/kg, i. p.) being used as an inducer for DM in experimental animals and treatment of quercetin (50 mg/kg, p.o.) and resveratrol (50 mg/kg, p.o.) alone and combination (1:1) was given for 21 days; glimepiride (0.09 mg/kg, p.o.) was used as standard antidiabetic agents for the present research. Biochemical parameters such as plasma glucose, serum lipid profile, creatinine, total protein, and albumin; liver glycogen content, and morphological parameters such as body weight were evaluated. Plasma glucose was evaluated on days 0, 7, 14, and day 21, and other biochemical and morphological parameters were measured at the start and the end of treatment respectively. Treatment with quercetin (Q) and resveratrol (R) alone and in combination showed a significant reduction in the levels elevated levels of plasma glucose, dyslipidemia, altered kidney parameters with improvement in the body weight and glycogen content in the liver. Whereas; resveratrol- quercetin (RQ) in combination with glimepiride depicted a significant (p<0.001) decline in plasma glucose, dyslipidemia, altered kidney function, and improvement in body weight and liver glycogen content when compared with untreated diabetic animals.Phytoconstituents such as quercetin and resveratrol possess prominent antidiabetic activity owing to their antidiabetic mechanism of glucose utilization and insulin secretagogue-like activity. The combination of quercetin and resveratrol was highly beneficial as a supportive treatment for diabetes and associated complication. Keywords: Diabetes, Plasma glucose, Quercetin, Resveratrol